Pengaruh Orientasi Pembelajaran Dan Orientasi Kewirausahaan Terhadap Pertumbuhan Perusahaan Pada Ukm Batik Di Gedung Smesco Jakarta - Thingdiacia Tjen; Mei Ie (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to determine the effect of learning orientation and entrepreneurial orientation on the growth of batik SME companies in Smesco Jakarta building. This study uses a reference to the theory of